A multi-model assessment for the 2006 and 2010 simulations under the Air Quality Model Evaluation International Initiative (AQMEII) phase 2 over North America: Part I. Indicators of the sensitivity of O3 and PM2.5 formation regimes. (August 2015) - Campbell, Patrick; Zhang, Yang; Yahya, Khairunnisa; Wang, Kai; Hogrefe, Christian; Pouliot, George; Knote, Christoph; Hodzic, Alma; San Jose, Roberto; Perez, Juan L.; Jimenez Guerrero, Pedro; Baro, Rocio; et al.
Abstract: Under the Air Quality Model Evaluation International Initiative, Phase 2 (AQMEII-2), three online-coupled air quality model simulations, with six different configurations, are analyzed for their performance, inter-model agreement, and responses to emission and meteorological changes between 2006 and 2010. In this Part I paper, we focus on evaluating O3 and PM2.5 indicator-based analyses, which are important in the development of applicable control strategies of O3 and PM2.5 pollution in different regions worldwide. The O3 indicators agree on widespread NOx -limited and localized VOC-limited conditions in the U.S. The NOy and O3 /NOy indicators overpredict the extent of the VOC-limited chemistry in southeast U.S., but are more robust than the H2 O2 /HNO3, HCHO/NOy, and HCHO/NO2 indicators at the surface, which exhibit relatively more inter-model variability. The column HCHO/NO2 indicator is underpredicted in the O3 and non-O3 seasons, but there is regional variability. For surface PM2.5 indicators, there is good inter-model agreement for the degree of sulfate neutralization; however there are systematic underpredictions in the southeast U.S. There is relatively poor inter-model agreement for the less robust adjusted gas ratio indicator, which is largely overpredicted in the summer and both under- and overpredicted in winter in the southeast U.S. There is good inter-model agreement for the O3 indicator sensitivities, indicating a predominant shift to more NOx -limited conditions in 2010 relative to 2006. There is less agreement for PM2.5 indicator sensitivities, which are less robust, while indicating shifts to either regime due to different responses of aerosol treatments to changes in emissions and meteorology. Highlights: A multi-model evaluation of O3 and PM2.5 indicators is presented for North America. Widespread NOx -limited regimes during May–September, and localized VOC-limited. Overprediction in the extent of VOC-limited chemistry in southeast U.S. NOy and O3 /NOy are the most robust O3 indicators. PM2.5 indicators are less robust than O3 indicators.